Business characteristics of selected farms in Mymensingh and Kushtia - Jabbar, M. A. (Mohammad Abdul), 1947- (Research report (Bangladesh Agricultural University. Bureau of Socio-economic Research and Training) ;, 1978)
Report of a 1974-1975 survey conducted in selected agricultural farms of Mymensingh and Kushtia districts.